2012
DOI: 10.1002/sd.1548
|View full text |Cite
|
Sign up to set email alerts
|

Governing Innovation for Sustainable Development in the Danish Biogas Sector – a Historical Overview and Analysis of Innovation

Abstract: Drawing on innovation literature, this article contests the wisdom of the conventional linear innovation model (invention-demonstration-commercialization-diffusion) and argues that innovation in the case of biogas is, instead, characterized by numerous feedback loops between research, demonstration, commercialization and diffusion. Furthermore, these feedback loops are heavily influenced and shaped by public sector interventions in many aspects of the innovation activities. The article presents the history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…Biogas production has been developed in Denmark since the late 1970s [2], primarily based on manure and co-substrates from a large agricultural industry; and due to regulation biogas plants have primarily supplied heat and power locally.…”
Section: Biogas In Denmarkmentioning
confidence: 99%
See 1 more Smart Citation
“…Biogas production has been developed in Denmark since the late 1970s [2], primarily based on manure and co-substrates from a large agricultural industry; and due to regulation biogas plants have primarily supplied heat and power locally.…”
Section: Biogas In Denmarkmentioning
confidence: 99%
“…Biogas production have been developed in Denmark since the late 1970's with varying focus points [2]. Biogas is a renewable fuel that can be produced from a large variety of inputs such as manure, waste water and other wet substrates, which are expensive to use in other technologies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, innovation research often criticizes such simple linear innovation and development models, where research should lead to inventions that later are supposed to be demonstrated, commercialized, and diffused (Freeman, 1996). Instead, a more dynamic model involving feedback loops and intervention of different actors is seen as more realistic (Lybaek et al, 2012). Possibly, there is already an ongoing evolution of existing biofuel production into biorefinery networks, where existing biofuel industries develop their operations towards increased valorisation, productification and diversification.…”
Section: Future Outlookmentioning
confidence: 99%
“…However, the potential for biogas production and GHG reductions might not be realised although studies show that it exists and suggest how it could be realised. For example, Lybaek et al (2013) have shown how the dynamic and non-linear nature of the development process in this field means that basic biogas research does not automati-cally lead to technological innovation. This indicates that studying the production and use of biogas from more perspectives than purely technical ones is desirable.…”
Section: Biogasmentioning
confidence: 99%
“…The sustainable development of energy and transport systems requires policy support (e.g., Jacobsson and Karltorp, 2013;Lybaek et al, 2013;Magnusson, 2012a;Nykvist and Nilsson, 2014), and at least gets policy attention. National and European policy often includes measures to achieve climate goals, such as reaching the 2°C target.…”
Section: Research Question IImentioning
confidence: 99%